A new rhodamine‐based fluorescent chemodosimeter for mercuric ions in water media. (25th July 2014) - Quy, Phan Tu; Hien, Nguyen Khoa; Bao, Nguyen Chi; Nhan, Doan Thanh; Khanh, Dang Van; Nhung, Nguyen Thi Ai; Tung, Truong Quy; Luyen, Nguyen Dinh; Quang, Duong Tuan
Abstract A new rhodamine–ethylenediamine–nitrothiourea conjugate (RT) was synthesized and its sensing property as a fluorescent chemodosimeter toward metal ions was explored in water media. Analytical results from absorption and fluorescence spectra revealed that the addition of Hg2+ ions to the aqueous solution of the chemodosimeter RT caused a distinct fluorescence OFF–ON response with a remarkable visual color change from colorless to pink; however, no clear spectral and color changes were observed from other metal ions including: Zn2+, Cu2+, Cd2+, Pb2+, Ag+, Fe2+, Cr3+, Co3+, Ni2+, Ca2+, Mg2+, K+ and Na+. The sensing results and the molecular structure suggested that a Hg2+‐induced a desulfurization reaction and cyclic guanylation of the thiourea moiety followed by ring‐opening of the rhodamine spirolactam in RT are responsible for a distinct fluorescence turn‐on signal, indicating that RT is a remarkably sensitive and selective chemodosimeter for Hg2+ ions in aqueous solution. Hg2+ within a concentration range from 0.1 to 25 μM can be determined using RT as a chemodosimeter and a detection limit of 0.04 μM is achieved. Copyright © 2014 John Wiley & Sons, Ltd.